Time constraints limit group sizes and distribution in red and black-and-white colobus - Korstjens, A; Dunbar, R (Springer Science + Business Media, 2007)
Researchers have shown that, in frugivorous primates, a major constraint on group size is intra group feeding competition. The relationship is less obvious in folivorous primates. We investigated whether colobine group sizes are constrained by time limitations as a result of their low energy diet and ruminant-like digestive system. We used climate as an easy to obtain proxy for the productivity of a habitat. Using the relationships between climate, group size, and time budget components for populations of Colobus and Piliocolobus at different research sites, we created 2 taxon-specific models. In both genera, feeding time increased with group size or biomass. The models for Colobus and Piliocolobus correctly predicted the presence or absence of the genera at, respectively, 86% of 148 and 84% of 156 African primate sites. Median predicted group sizes where the respective genera were present are 19 for Colobus and 53 for Piliocolobus. We show that the differences between the 2 genera are due mainly to intrinsic differences in the way each taxon's digestive physiology interacts with climatic variables to influence resting time requirements. The models may help us explore their responses to climatic change in both the past and the future.